2021
DOI: 10.3233/jad-201584
|View full text |Cite
|
Sign up to set email alerts
|

Language Network Connectivity Increases in Early Alzheimer’s Disease

Abstract: Background: Language production deficits occur early in the course of Alzheimer’s disease (AD); however, only a few studies have focused on language network’s functional connectivity in mild cognitive impairment (MCI) due to AD. Objective: The current study aims to uncover the extent of language alteration at the MCI stage, at a behavioral and neural level, using univariate and multivariate analyses of structural MRI and resting-state fMRI. Methods: Twenty-four MCI due to AD participants and 24 matched healthy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 43 publications
6
11
3
Order By: Relevance
“…It is unclear what this reverse pattern indicates, but these findings suggest that HA and MCI groups may use different strategies to retrieve or process semantic information during the task. Nevertheless, the MCI group shows patterns of neural oscillations that can be differentiated from the HA group on the SORT task and these alterations may be indicative of early neural decompensation, as suggested in prior studies (Woodard et al, 2009;Barbeau et al, 2012;Pistono et al, 2021).…”
Section: Discussionsupporting
confidence: 54%
“…It is unclear what this reverse pattern indicates, but these findings suggest that HA and MCI groups may use different strategies to retrieve or process semantic information during the task. Nevertheless, the MCI group shows patterns of neural oscillations that can be differentiated from the HA group on the SORT task and these alterations may be indicative of early neural decompensation, as suggested in prior studies (Woodard et al, 2009;Barbeau et al, 2012;Pistono et al, 2021).…”
Section: Discussionsupporting
confidence: 54%
“…Compared to the normal group, a reduction in FC strength was found throughout the LN in the AD group. Neuroimaging studies in AD patients have shown that language disorders are associated with atrophy or hypometabolism in the left IFG and temporal regions 32,33 . Also, impairments in phonological processing are associated with damage to the left pSTG 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging studies in AD patients have shown that language disorders are associated with atrophy or hypometabolism in the left IFG and temporal regions. 32,33 Also, impairments in phonological processing are associated with damage to the left pSTG. 34 Possibly due to dysfunction and a lower FC between nodes of the network, a decrease in semantic and pragmatic processing may occur as the disease progresses.…”
Section: Language Networkmentioning
confidence: 99%
“…These changes also map onto altered network connectivity 19,20 including the semantic control network (SCN) 21 . Resting state functional MRI (rs‐fMRI) investigations have revealed alterations of functional connectivity (FC) in the cognitive control network (CCN) linked to linguistic abilities 22–24 . Since digital voice biomarkers may reflect both linguistic and speech changes, it is unclear if these novel biomarkers will map to previously known linguistic or speech brain networks.…”
Section: Introductionmentioning
confidence: 99%